Effect of reduced expiratory pressure on pharyngeal size during nasal positive airway pressure in patients with sleep apnoea: evaluation by continuous computed tomography. Issue 10 (October 1992) - Gugger, M; Vock, P
Abstract : BACKGROUND: This study aimed to determine whether reducing the expiratory pressure during nasal positive airway pressure for reasons of comfort causes a substantial decrease in the upper airway calibre. METHODS: Eight patients with obstructive sleep apnoea were studied. Continuous computed tomography (each run lasting 12 seconds) was used to measure minimum and maximum pharyngeal cross sectional areas at the velopharynx and the hypopharynx. Pharyngeal areas were measured while patients were awake and breathing without assistance, during the application of 12 cm H2O continuous positive airway pressure, and during bi-level positive airway pressure with an inspiratory pressure of 12 cm H2O and an expiratory pressure of 6 cm H2O. RESULTS: Nasal continuous positive airway pressure significantly increased the mean minimum and maximum upper airway areas at both the velopharynx and the hypopharynx compared with normal unassisted breathing. Bi-level positive airway pressure did not show a statistically significant increase in the minimum upper airway area at either level compared with normal unassisted breathing. The minimum areas of the velopharynx and hypopharynx were smaller with bi-level than continuous positive airways pressure in six of eight and eight of eight patients respectively but these were still greater than during unassisted breathing in seven of eight and six of eight patients respectively. CONCLUSIONS: Continuous positive airway pressure at 12 cm H2O is more effective in splinting the pharynx open than bi-level positive airway pressure with an inspiratory positive airway pressure of 12 cm H2O and an expiratory pressure of 6 cm H2O in patients with obstructive sleep apnoea during wakefulness, suggesting an important role for expiratory positive airway pressure. The clinical importance of this finding needs to be evaluated during sleep.